Peningkatan Motivasi Belajar Bahasa Arab melalui Strategi Game-Based Learning Berbasis Spin Wheel - Ilham, Affan Hadian; anwar, Najih Anwar (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2025)
This study aims to analyze the effectiveness of the Game-Based Learning (GBL) strategy using a spin wheel to enhance students' motivation in learning Arabic at SD Muhammadiyah 1 Krian. The method used was Classroom Action Research (CAR) based on the Kurt Lewin model, conducted in two cycles. Data collection instruments included questionnaires, observations, interviews, and documentation. The results showed an increase in students’ learning motivation from 55% (categorized as moderate) in the initial condition, to 68% (strong) in the first cycle, and 86% (very strong) in the second cycle. These findings indicate that the spin wheel-based GBL approach is effective in increasing students' motivation in learning Arabic.